Parasite exchange and hybridisation at a wild-feral-domestic interface - Smith, WJ; Jezierski, MT; Dunn, JC; Clegg, SM (Elsevier, 2023)
Interactions between wild, feral, and domestic animals are of economic and conservation significance. The pigeon Columba livia is a synanthropic species in a feral form, but it also includes the rare Rock Dove. Columba livia is an important player at the wild-domestic interface, acting as a carrier of avian diseases, and the feral form threatens Rock Doves with extinction via hybridisation. Despite its abundance, little is known about drivers of disease prevalence in C. livia, or how disease and hybridisation represent synergistic threats to Rock Doves. We focused on infection by the parasite Trichomonas, first collating prevalence estimates in domestic and free-living populations from relevant studies of C. livia. Second, we characterised variation in the diversity and prevalence of Trichomonas among three C. livia populations in the United Kingdom: a feral, a Rock Dove, and a feral-wild hybrid population. Across multiple continents, free-living pigeons had lower Trichomonas infection than captive conspecifics, but the effect was weak. Environmental factors which could impact Trichomonas infection status did not explain variation in infection among populations. Among the British populations, strain diversity varied, and there was lower parasite prevalence in Rock Doves than feral pigeons. Individual infection status was not explained by the available covariates, including hybrid score and site. The drivers of Trichomonas prevalence are unclear, perhaps due to idiosyncratic local-scale drivers. However, given the population-level variation in both infection prevalence and introgressive hybridisation, the potential combined effects could accelerate the extinction of the Rock Dove. Further study of the synergistic effects of multiple types of biotic interactions at the wild-feral-domestic interface is warranted, especially where vagile, globally distributed and superabundant animals are involved.